Estrategia de eficiencia de la nutrición en cacao (Theobroma cacao L.) clon EETP-800, 801 y CCN51 en la provincia de Zamora Chinchipe, sector “El Padmi" - Auquilla Yangua, Claudia Liliana (2022)
Despite being one of the world's largest cocoa producers, Ecuador suffers from low yields in comparison to other Latin American countries. In order to improve the crop's development and production, nutritional strategies are needed, including the use of biostimulants. This research aimed to evaluate the effect of nutrition strategies on the production and yield of cocoa (Theobroma cacao L.) clone EETP800, EETP801 and CCN51. To accomplish this purpose, a study was carried out at the experimental station "El Padmi" of the National University of Loja, using plants of approximately 2 years of age, with a planting density of 3.5 m x 4 m, under a completely randomized block design, with nine treatments and four replications. Humic substances and algae extract were used as biostimulants at a dose of 21 ml/plant and 1.4 ml/plant, respectively, applied to the three clones, and a control without the application of biostimulant was also used. The variables evaluated were: number of ears per tree, ear length and width, diameter and cross-sectional area of the trunk, bromatological characteristics of the kernel, production, yield, leaf area index (LAI), stomatal conductance, chlorophyll, pH and electrical conductivity of the soil. The results showed that no significant differences were found between the tratments in length, cob width and weight, number and weight of kernels, yield, crown diameter, LAI and stomatal density; yet, there was an effect of genotype and biostimulant interaction on the yield, where the EETP801 genotype with the application of humic acid obtained 886.43 kg/ha. Regarding the fat content, CCN51 obtained 37.65%, unlike the rest. The application of humic acids generated a higher yield, but a moderately acid effect on soil pH was observed, a factor to consider and analyze in the case of continuous applications. Key words: Theobroma cacao L, nutrition, yield, biostimulants, humic acid, algae extract.